Grab-cut Algorithm in Machine Learning for Diagnosing Melanoma - Veeralakshmi, R; Jeyalakshmi, T Ratha (International Journal of Computer Sciences and Engineering, 2025)
Collected data directly from examples, data, and past experience is called Machine Learning. Cancer diagnosing could be an extremely difficult field in Machine Learning. Skin cancer is nothing but it be a dangerous disease associated it’s found as an uncontrolled growth of abnormal skin cells. Image enhancement method is utilized to remove unwanted scales (median filtering and salt and pepper technique) in image. Then the projected methodology helps in the section of cancer footage. Finally, Principal component Analysis is employed to concentrates on the melanoma’s exists and Grab cut methodology is utilized for the feature extraction of melanoma mole from skin.